Improved Nanophotonic Front Contact Design for High‐Performance Perovskite Single‐Junction and Perovskite/Perovskite Tandem Solar Cells. Issue 10 (12th September 2021) - Hossain, Mohammad Ismail; Shahiduzzaman, Md.; Saleque, Ahmed Mortuza; Huqe, Md. Rashedul; Qarony, Wayesh; Ahmed, Safayet; Akhtaruzzaman, Md.; Knipp, Dietmar; Tsang, Yuen Hong; Taima, Tetsuya; Zapien, Juan Antonio
Abstract : The front contact of solar cells greatly influences the optoelectronic performance of perovskite solar cells (PSCs) by controlling the coherent light propagation as well as charge transport within the device. Herein, the nanophotonic front contact consisting of multilayer nanodomes and nanoholes for high‐efficiency perovskite single‐junction and perovskite/perovskite tandem solar cells (PVK/PVK TSCs) is investigated. The optical and electrical characteristics of solar cells are investigated by conducting an advanced 3D numerical approach with the combination of finite‐difference time‐domain (FDTD) and finite‐element method (FEM) simulations embedded with the particle swarm optimization (PSO) algorithm. The numerical modeling is validated by fabricating a set of efficient PSCs, optimized to a power conversion efficiency (PCE) of 17.9%, V OC of 1.07 V, J SC of 21.8 mA cm −2 and fill factor (FF) of 77%. The nanophotonic device results in improved J SC by 10−15%, resulting from 10−15% enhanced light incoupling compared with the planar device, while also strengthening the omnidirectional capabilities at angles of illumination as high as 40°. The optimized nanophotonic front contact results in PCEs of >23% and >30% (matched J SC ≈18 mA cm −2 ) for single‐junction PSCs and PVK/PVK TSCs, respectively. Details of the nanophotonic front contact, device, and fabrication process are provided. Abstract : The nanophotonic perovskite solar cell covered with an array of nanodome or nanohole structures can provide enhanced light incoupling compared with the planar device, resulting in improved J SC by ∼10–15% and strengthening of the omnidirectional capabilities. Such optimized nanophotonic front contacts can benefit from realizing 30% power conversion efficiency in the case of perovskite/perovskite tandem solar cells.